Experimental study on atomization characteristics and dust-reduction performance of four common types of pressure nozzles in underground coal mines - Han Han; Pengfei Wang; Ronghua Liu; Chang Tian (International Journal of Coal Science & Technology, 2020)
Abstract Pressure nozzle is commonly used in the dust-reduction techniques by spraying of underground coal mines. Based on the internal structure, the pressure nozzle can be divided into the following types: spiral channel nozzle, tangential flow-guided nozzle and X-swirl nozzle. In order to provide better guidance on the selection of nozzles for the coal mine dust-reduction systems by spraying, we designed comparing experiments to study the atomization characteristics and dust-reduction performance of four commonly used nozzles in the coal mine underground with different internal structures. From the experimental results on the atomization characteristics, both the tangential flow-guided nozzle and the X-swirl nozzle have high flow coefficients. The atomization angle is the largest in the spiral non-porous nozzle, and smallest in both the X-swirl nozzle and the spiral porous nozzle. The spraying range and the droplet velocity are inversely proportional to the atomization angle. When the water pressure is low, the atomization performance of the spiral non-porous nozzle is the best among the four types of nozzles. The atomization performance of the X-swirl nozzle is superior to other types when the water pressure is high. Under the high water pressure, the particle size of the atomized droplets is smallest in the X-swirl nozzle. Through the experiments on the dust-reduction performance of the four types of nozzles and the comprehensive analysis, the X-swirl nozzle is recommended for the coal mine application site with low water pressure in the dust-reduction system, while at the sites with high water pressure, the spiral non-porous nozzle is recommended, which has the lowest water consumption and obvious economic advantages.